Adsorptive recovery of palladium(ii) from aqueous solution onto cross-linked chitosan/montmorillonite membrane. Issue 57 (26th May 2016) - Liu, Jian; Zheng, Liuchun; Li, Yaowei; Free, Michael; Yang, Mingzhu
Abstract : A cross-linked chitosan/montmorillonite (CCTS-M) membrane was prepared successfully with a glutaraldehyde cross-linker, and then was characterized by FTIR, XRD, SEM/EDX, TG/DTG and XPS. Abstract : A cross-linked chitosan/montmorillonite (CCTS-M) membrane was prepared successfully with a glutaraldehyde cross-linker, and then was characterized by FTIR, XRD, SEM/EDX, TG/DTG and XPS. The materials were used for removing palladium(ii ) from aqueous solutions. The effect of variable parameters including initial pH, contact time, initial concentration, and temperature were investigated. The results showed that the maximum capacity of the membrane was 193 mg g −1 at pH 2. This article not only described the adsorption behavior but also suggested isotherms, the kinetics data were best modeled using pseudo-second-order model, and the Langmuir isotherm model could fit the experimental data well. The thermodynamic parameters Δ G ° (<0) and Δ H ° (>0) indicated that the adsorption was a spontaneous and endothermic process. FTIR and XPS techniques confirmed that the –NH3 +, –NH2 and CN– functional groups in the CCTS-M membrane played prominent roles in the adsorption process. Our results revealed that the membrane could be a promising adsorbent for the recovery of palladium.